Rasio Fundamental dan Harga Saham: Kebijakan Dividen sebagai Variabel Mediasi - Ila Nadilah; Siti Mudawanah; Pindonta Nalsal Purba (Owner : Riset dan Jurnal Akuntansi, 2026)
This study investigates the effect of Debt to Equity Ratio (DER), Earning Per Share (EPS), and Economic Value Added (EVA) on stock prices, with dividend policy proxied by the Dividend Payout Ratio (DPR) as a mediating variable in automotive sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This research is motivated by inconsistent findings in prior studies regarding the effectiveness of financial fundamentals and dividend policy in influencing stock price formation, particularly in emerging markets during the post-pandemic recovery period. Previous studies have predominantly focused on direct relationships between financial ratios and stock prices, while limited research has examined dividend policy as a transmission mechanism linking firm fundamentals and market valuation within the automotive industry context. This study contributes to the Signalling Theory literature by examining whether dividend policy acts as an effective transmission mechanism between firm fundamentals and stock price formation in the post-pandemic automotive industry. The automotive sector was selected because it represents a capital-intensive industry highly sensitive to leverage, macroeconomic instability, interest rate fluctuations, and changes in consumer purchasing power following the COVID-19 pandemic.The study employed a quantitative approach using panel data regression analysis with secondary data obtained from annual reports of 11 automotive sub-sector companies selected through purposive sampling, resulting in 55 firm-year observations. The analysis was conducted using EViews 13. The study applied Fixed Effect Model (FEM) and Random Effect Model (REM) estimations based on Chow, Hausman, and Lagrange Multiplier tests. Mediation analysis was further examined using the Sobel test. The results reveal that EPS has a positive and significant effect on stock prices, indicating that investors in the Indonesian capital market remain strongly profit-oriented and respond primarily to accounting-based profitability signals. In contrast, DER, EVA, and DPR do not significantly affect stock prices. The findings also show that DER negatively affects DPR, EVA positively affects DPR, while EPS unexpectedly exhibits a negative effect on DPR. Furthermore, dividend policy fails to mediate the relationship between DER, EPS, EVA, and stock prices. The findings provide theoretical implications by demonstrating that not all financial indicators generate equally strong market signals in emerging capital markets. Investors tend to respond more directly to profitability signals rather than dividend distribution signals. Practically, this study suggests that investors should prioritize profitability and operational efficiency indicators when making investment decisions, while corporate managers should focus on strengthening financial performance and long-term business sustainability rather than relying solely on dividend policy to influence market valuation...